PENGARUH PENGGUNAAN GADGET TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI SISWA KELAS XI IPS DI SMA NEGERI 3 KOTA JAMBI - Benar Sembiring, Dewi Puji Astuti (Universitas Batanghari Jambi, 2019)
Abstract This study aims to determine the description and influence of the use of gadgets and student learning outcomes in economic subjects of class XI IPS students in SMA Negeri 3 Kota Jambi. The design of this study uses quantitative descriptive. The population used was 74 respondents of XI IPS students in SMA Negeri 3 Jambi City, while the research sample used was all respondents of XI IPS students in SMA Negeri 3 Jambi City. The results obtained that the indicator that has the greatest value is the use of gadgets to find information with a value of 83.32 with a good category. Meanwhile, it is also known that the use of gadgets has an effect on student learning outcomes obtained from research that has been carried out. Where students still use gadgets during economic subject hours. This means that it will affect student learning outcomes and will cause problems in the learning process. Keywords : Gadgets, Learning Outcomes